Transformational Leadership in Managing Multigenerational Teachers in an Islamic Primary School - Rizkarima Rizkarima; Mulyawan Safwandy Nugraha (Lembaga Ta'lif wa An-Nasyr (LTN) PBNU, 2025)
This study examines how a madrasah principal practices transformational–relational leadership in managing multigenerational teachers and the implications for teacher performance and institutional achievement. Generational diversity among teachers increasingly influences organizational dynamics through differences in work values, communication styles, and professional expectations. In Islamic educational institutions, these challenges are further shaped by the integration of managerial practices with religious and moral values. Employing a qualitative case study design, the research was conducted at MI Al-Inayah Kota Bandung to capture in-depth leadership practices within a specific multigenerational context. Data were collected through semi-structured interviews, questionnaires, and document analysis, and analyzed using descriptive qualitative techniques supported by data triangulation. The findings show that transformational–relational leadership functions as a foundational mechanism for aligning teachers across generations through shared vision, relational trust, and psychological safety. Leadership practices emphasizing empathy, role modeling, and inclusive communication enable the constructive management of generational differences. Competency-based and collaborative strategies support effective role distribution, cross-generational collaboration, and mutual learning. These practices contribute to increased teacher motivation, strong professional loyalty, low turnover, and sustained achievement in madrasahs. This study extends transformational leadership discourse in a multigenerational Islamic education context and offers practical leadership strategies for managing generational diversity.